P096 Subjective ratings of medication strength of lemborexant over 6 months in subjects with moderate or severe insomnia. (7th October 2021) - Drake, C; Yardley, J; Pinner, K; Moline, M
Abstract: Introduction: In Study 303 (SUNRISE-2), significantly more subjects reported a positive effect of lemborexant (LEM), a dual orexin receptor antagonist, versus placebo (PBO) on their sleep at 1mo, 3mo and 6mo, as assessed by items 1–3 of the Patient Global Impression–Insomnia (PGI-I). LEM-treated subjects also reported larger and statistically significant decreases in the Insomnia Severity Index (ISI) versus PBO. This analysis examined potential LEM tolerance via patient-reported ratings of medication strength on PGI-I item 4 in subjects with moderate/severe insomnia. Methods: In this 12mo double-blind, PBO-controlled (first 6mo), phase 3 study, subjects ≥18y with insomnia disorder and ISI scores ≥15 were randomized to PBO (n=318) or LEM (5mg, [LEM5], n=316; 10mg, [LEM10], n=315). The ISI and PGI-I were administered at 1mo, 3mo and 6mo. Results: The percentage of subjects with moderate (ISI=15–21; n=692) or severe (ISI=22–28; n=223) insomnia at baseline who rated LEM as "just right" increased from 1mo (moderate: LEM5=46.4%; LEM10=43.3%; PBO=31.3%; severe: LEM5=35.8%; LEM10=40.6%; PBO=15.0%) to 6mo (moderate: LEM5=56.5%; LEM10=53.9%; PBO=39.7%; severe: LEM5= 54.8%; LEM10=55.4%; PBO=21.6%). Ratings of "too weak" decreased over 6 months in both ISI severity groups. PBO group ratings of "too weak" always exceeded the LEM groups by >15%. Ratings of "too strong" were low and stable over time. Conclusions: Findings suggest that LEM tolerance does not occur over 6mo with either LEM dose since patient perceptions of LEM treatment being "too weak" did not increase over the study period. These data support the persistent efficacy of long-term LEM treatment for chronic insomnia.